A Value-Added Study of Teacher Spillover Effects Across Four Core Subjects in Middle Schools - Kun Yuan (Arizona State University, 2015)
This study examined the existence, magnitude, and impact of teacher spillover effects (TSEs) across teachers of four subject areas (i.e., mathematics, English language arts [ELA], science, and social studies) on student achievement in each of the four subjects at the middle school level. The author conducted a series of value-added (VA) analyses, using multiple years of state achievement test scores in the four tested subjects for students at grades 7 and 8 from an urban school district in the Southern US. Results showed evidence that mathematics and ELA teachers jointly contributed to student achievement in mathematics and ELA. ELA teachers also showed TSEs on student achievement in science (at grade 8 only) and social studies (at both grade levels), with ELA teachers' effect sizes close to or even greater than those of the own-subject teachers at grade 8. Results also showed that controlling for TSEs slightly decreased the variation and precision of teachers' VA scores and changed the quartile rankings of individual teachers' VA scores for a non-negligible group of teachers (11%-25%). On average, the percentage of teachers whose VA rankings were affected due to controlling for TSEs was greater for test subjects with TSEs than subjects without TSEs. Results challenge the current practice of ignoring teachers' TSEs when estimating teachers' VA scores. Results also support the use of group-based incentive plan when rewarding secondary mathematics and ELA teachers based on student achievement growth in these two subjects.